Interaksi Manusia Dengan Alien Dan Peranan AI Dalam Novel Only Human Karya Sylvain Neuvel - Diky Ajie Andriana; Maksilino Devaldo Siletty; Eva Dwi Kurniawan (Journal Islamic Global Network for Information Technology and Entrepreneurship, 2024)
The science fiction novel "Only Human" by Sylvain Neuvel summarizes the journey of humans and artificial intelligence (AI) in interacting with alien creatures on a mysterious planet. This research uses a hermeneutic method to deepen understanding of the story context. The main focus of research is the character of AI, Technology, Robots and Aliens which play a central role in facilitating communication between humans and aliens. In this case it explores how the presence of AI supports human efforts to understand very alien culture and technology. In the process of analysis, we also explore the ethical and moral aspects that arise along with the use of AI in the context of intersex relationships. With a hermeneutic method, highlighting how contextual interpretation and understanding enriches the analysis of the complex dynamics between humans, AI, and aliens. This research provides in-depth insight into the concepts of artificial intelligence, technology, robots, and aliens in the narrative "Only Human," which is expected to stimulate further thinking about the future of human interaction with artificial intelligence and extraterrestrial life.